A perspective on dental activity during COVID‐19: The Italian survey. (15th September 2020) - Izzetti, Rossana; Gennai, Stefano; Nisi, Marco; Barone, Antonio; Giuca, Maria Rita; Gabriele, Mario; Graziani, Filippo
Abstract: Objectives: During the months of March and April 2020, Italy saw an exponential outbreak of COVID‐19 epidemic. Dental practitioners were particularly limited in their routine activity, and the sole performance of urgent treatments was strongly encouraged during the peak of the epidemic. A survey among dental professionals was performed between 6th and 13th of April, in order to evaluate the status of dental practice during COVID‐19 in Italy. Materials and Methods: An online anonymous questionnaire was administered to retrieve data on the dental procedures performed, the preventive measures adopted, and the predictions on the future changes in dentistry following the pandemic. Results: The survey was completed by 3, 254 respondents and, according to the results obtained, dental activity was reduced by the 95% and limited to urgent treatments. The majority of the surveyed dentists employed additional personal protective equipment compared to normal routine, although in a non‐negligible number of cases difficulty in retrieving the necessary equipment was reported. Conclusions: The survey provided a snapshot of dental activity during the SARS‐CoV‐2 outbreak. Overall, following the peak of the epidemic, it is probable that dental activities will undergo some relevant changes prior to fully restart.